As an Alternative - Tanrisever, Canan (IGI Global, 2020)
Tourist guidance training/education is different in many countries of the world. Tourism types or tourism choices affect the specialization areas of tourist guides. Tourist guides that should be one of the components of an ecologically based integrity are not yet included in all routes. This area, which is not included in the tourist guidance curriculum, has been proposed as a training module for specialization in this study. In this context, the aim of the study is to contribute to the field and literature by creating the infrastructure of the cultural routes education program as a module. The study is a heuristic research. The interview form used in the research was formed by utilizing expert opinions on qualitative data collection methods based on literature review. According to the results of this research, this module is divided into seven main topics.
Keywords: 4. Education; 11. Sustainability; 8. Economic growth; 10. No inequality; 12. Responsible consumption